A conceptual framework to excogitate agile from lean transformation. (2nd August 2010) - Gadalla, Mohamed A.
Manufacturing system transformation becomes a necessity to overcome increased competition. Lean vs. agile transformation is an increased debatable issue in the manufacturing community. Combining lean and agile adds more myth to the issue. Continuous improvement initiatives such as: adopting lean principles, Six Sigma, QFD, TQM, etc. raise an important question about these initiatives being adequate. This work introduces the concept of excogitating agile transformation from an initiated lean transformation through finding a pathway between the two. It further extends the concept to a series of suggested transformable steps that forms roadmap for a company to reach agility.